PENGARUH PEMBERIAN KOMPRES HANGAT TERHADAP INTENSITAS NYERI PADA IBU BERSALIN KALA I FASE AKTIF DI RB. MARDI RAHAYU SEMARANG - Wulandari, Priharyanti; Kustriyani, Menik; Chasanah, Uswatun (Universitas Muhammadiyah Semarang, 2017)
Background : Labor pain is a pain that occurs the activity in body to put out the infant where the contraction pain start from bottom of back then spread to the bottom of stomach. Based on phenomenon above, researcher interested to give warm compress therapy on bottom of back for 20 minutes was considered can relieve labor pain. The purpose was to know the giving of warm compress to the intensity of pain in maternal stage I of active phase in RB. Mardi Rahayu Semarang. Methode : Quantitative research with experimental One Group Pretest-Posttest Without Control Design. Sampling technique used total sampling of 30 maternals per month. Data was obtained with Wilcoxon statistic test. Result : Based on Wilcoxon test was known Zcount = -5,069 and Ztablewas 1,69 and p value = 0,000 with ? = 0,05. Where p value 0,000 < 0,05 then Ho was rejected, Ha was accepted. Conclusion : There was an effect of the giving of warm compress to the intensity of pain in maternal stage I of active phase in RB. Mardi Rahayu Semarang.Keywords : Maternal, Labor Pain, Warm Compress